IDDF2019-ABS-0210 Preliminary efficacy and safety of 8-week glecaprevir/pibrentasvir in patients with HCV genotype 1–6 infection and compensated cirrhosis: the EXPEDITION-8 study. (June 2019) - Brown, Robert S; Hezode, Christopher; Wang, Stanley; Buti, Maria; Chuang, Wan-Long; Aguilar, Humberto; Horvath, Gabor; Carrion, Barbara Rosado; Rodriguez-Perez, Federico; Cohen, Eric; Hu, Yiran B; Schnell, Gretja; et al.
Abstract : Background: The pangenotypic direct-acting antivirals glecaprevir (identified by AbbVie and Enanta) coformulated with pibrentasvir (G/P) are approved to treat chronic HCV genotype (GT) 1–6 infection. Eight-week G/P achieved high SVR12 rates in Phase 2 and 3 studies, but was not studied in patients with compensated cirrhosis. Based on the high SVR12 rates demonstrated in treatment-naive patients with HCV GT1–6 infection and compensated cirrhosis treated with 12-week G/P, this study evaluates the efficacy and safety of an 8-week G/P treatment duration in that population. Methods: EXPEDITION-8 is an ongoing phase 3, non-randomized, single arm, open-label, multicenter study conducted in adults with chronic HCV GT1–6 infection with compensated cirrhosis who are HCV treatment-naive. A recently approved protocol amendment enabled the inclusion of HCV GT3-infected patients, who are not included in this analysis. G/P (300 mg/120 mg) is being dosed orally once-daily with food for 8 weeks. The primary efficacy endpoint is the SVR12 rate. Secondary endpoints are the on-treatment virologic failure and relapse rates. Adverse events and clinical laboratory abnormalities are being monitored in all patients. Results: In total, 280 treatment-naive patients with compensated cirrhosis have enrolled and are included in the analysis. To date, 116 patients have completed the post-treatment week 12 visit; (figure 1 ) shows preliminary efficacy results for those with available post-treatment week 4 and/or 12 data. No virologic failures have occurred. Adverse events (AEs) have been mostly mild, with the most common (at least 5%) AEs being pruritus and fatigue (both 9%), headache (7%) and nausea (6%). No AEs have led to discontinuation of G/P; 5 serious AEs have occurred, none of which were deemed related to G/P. Conclusions: In this ongoing study, G/P for 8 weeks in treatment-naive patients with HCV infection and compensated cirrhosis has been well-tolerated and achieved high rates of SVR, with no virologic failures to date. Updated efficacy and safety data will be presented at the meeting.